Endometrial Scratching by an Office Hysteroscopy for Unexplained Infertility: Predictors of Success and Pregnancy Rate - Zeena Helmi; Wassan Nori; Rana Raad Helmi (AlQalam Journal of Medical and Applied Sciences, 2024)
One-half of the infertile couples have unexplained infertility. The endometrial scratch (es) is believed to cause favorable endometrial inflammation, making it more receptive to an implanted embryo. We aimed to assess the success rate of es in enhancing pregnancy and to identify potential predictors for the successful outcome in couples with unexplained infertility. A case-series study included 268 couples with unexplained infertility attending the university teaching hospital in Baghdad for one year after es by an office hysteroscopy. Patients' socio-demographic factors, fertility history, and history of curettage were studied—the success of getting spontaneous pregnancy after es was studied as the dependent variable. SPSS statistical software was used, and the confidence level was employed to verify reliable predictors. The success rate following es was 44 (16.4%), confirmed by clinical pregnancy. There was a 5% decrease in the success rate of the es for every one-year increase in the female age; risk ratio (rr): 0.95; 95% ci 0.907- 0.995). The previous history of curettage increased the rate of the intervention’s success by more than two times (rr: 2.412; 95% ci: 1.181 - 4.926). Endometrial scratching improved the odds of pregnancy for couples with unexplained infertility. Potential predictors of the success were younger aged females and previous history of curettage. نصف الأزواج المصابين بالعقم لديهم عقم غير مبرر. يعتقد أن خدش بطانة الرحم (ES) يسبب التهاب بطانة الرحم المواتية، مما يجعله أكثر تقبلا للحمل. نهدف إلى تقييم معدل نجاح خدش بطانة الرحم في تعزيز الحمل وتحديد التنبؤات المحتملة بالنتيجة الناجحة لدى الأزواج الذين يعانون من العقم غير المبرر. شملت الدراسة سلسلة حالات لعدد من الازواج (268) زوجا يعانون من العقم غير المبرر الذين يحضرون مستشفى الجامعة التعليمي في بغداد لمدة عام واحد بعد خدش بطانة الرحم عن طريق تنظير الرحم. تمت دراسة العوامل الاجتماعية والديموغرافية للمرضى والتاريخ المرضي للخصوبة ولإجراء الكحت الرحمي أدى الى نجاح الحصول على الحمل التلقائي بعد دراسة خدش بطانة الرحم كمتغير تابع. تم استخدام برنامج SPSS الإحصائي، وتم استخدام مستوى الثقة للتحقق من التنبؤات الموثوقة. كان معدل النجاح بعد خدش بطانة الرحم (16.4٪). أكده الحمل السريري. كان هناك انخفاض بنسبة 5٪ في معدل نجاح خدش بطانة الرحم لكل زيادة لمدة عام واحد في عمر الإناث؛ نسبة المخاطر (RR): 0.95: 95٪ CI 0.907- 0.995). زاد التاريخ السابق للكشط من معدل نجاح التدخل بأكثر من مرتين (RR: 2.412؛ 95٪ CI: 1.181 - 4.926). أدى خدش بطانة الرحم إلى تحسين احتمالات الحمل للأزواج الذين يعانون من العقم غير المبرر. كان المتنبئون المحتملون بالنجاح هم الإناث الأصغر سنا والتاريخ السابق للكحت